Web portal for schools (WPFS) / Saim Yeong Harng - Saim , Yeong Harng (2004)
Web Portal For Schools (WPFS) is a web-based school management system. It is one of the smart school's concepts to integrate all the school management stuffs into an electronic environment. It is a revolution of the traditional school management system. The objectives of WPFS include: